2018
DOI: 10.3899/jrheum.171006
|View full text |Cite
|
Sign up to set email alerts
|

Longterm Safety and Efficacy of Adalimumab and Infliximab for Uveitis Associated with Juvenile Idiopathic Arthritis

Abstract: Objective.Anti-TNF-α agents have significantly changed the management of juvenile idiopathic arthritis (JIA). We evaluated the safety and efficacy of adalimumab (ADA) and infliximab (IFX) for the treatment of JIA-associated uveitis in patients treated for ≥ 2 years.Methods.Patients with JIA-associated uveitis treated with IFX and ADA were managed by a standardized protocol and data were entered in the ORCHIDEA registry. At baseline, all patients were refractory to standard immunosuppressive treatment or were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 14 publications
2
38
0
Order By: Relevance
“…77 Adalimumab was also shown to be better tolerated, with six patients in the study switching from infliximab to adalimumab due to infusion reactions or difficulty complying with infliximab. Recent studies with long-term follow up also conclude that adalimumab showed a superior efficacy and safety profile than infliximab, 78,79 and these results coincide with previous comparative studies between the two agents. 80,81 In contrast to these studies, two large retrospective studies showed that efficacy is similar and sustained regardless of the TNF-α inhibitor used, with no statistically significant difference in the response rates between infliximab and adalimumab.…”
Section: Comparative Studies Between Tnf-α Inhibitorssupporting
confidence: 85%
“…77 Adalimumab was also shown to be better tolerated, with six patients in the study switching from infliximab to adalimumab due to infusion reactions or difficulty complying with infliximab. Recent studies with long-term follow up also conclude that adalimumab showed a superior efficacy and safety profile than infliximab, 78,79 and these results coincide with previous comparative studies between the two agents. 80,81 In contrast to these studies, two large retrospective studies showed that efficacy is similar and sustained regardless of the TNF-α inhibitor used, with no statistically significant difference in the response rates between infliximab and adalimumab.…”
Section: Comparative Studies Between Tnf-α Inhibitorssupporting
confidence: 85%
“…3 TNF-α inhibitors showed to be effective in different forms of (childhood) uveitis. [4][5][6][7][8] They are, however, being given with caution in case of traditional IMT failure because of reports on demyelination in patients with non-anterior uveitis. Therefore, in all patients with non-anterior uveitis, an MRI scan of the brain is recommended before starting TNF-α inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…Baseline n = 7 6 months n = 7 P-value b 12 months n = 6 P-value b FA CME a 3 (1-4) 0 (0-1) .017 0.5 (0-1.25) .027 FA capillary leakage a 7.0 (6-10) 4.0 (0-7) .017 2.5 (0.75-4.25) .028 FA vasculitis a 2 (1-3) 1 (0-2) .034 0 (0-0.5) .056 FA optic disc leakage a 2 (0-3) 1 (0-2) .034 1 (0-2) .083 FA total score a 14 (10)(11)(12)(13)(14)(15)(16)(17)(18) 8 (2)(3)(4)(5)(6)(7)(8)(9) .018 5 (1. Data given as median (interquartile range).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DMARDs, methotrexate being the most commonly employed, should be initiated in patients unresponsive to corticosteroids and it is recommended that early initiation of immunosuppressive treatment should be considered in children with active uveitis with already established complications at the time of diagnosis. 4,[24][25][26] Complications of pediatric uveitis are band keratopathy, cataracts, synechia, glaucoma, cystoid macular edema, retinal detachment, neovascularization of retina, optic disc and iris, decreased visual acuity, and loss of vision. These complications have been reported to be seen in more than half of the patients.…”
Section: Discussionmentioning
confidence: 99%